Authenticity perceptions, brand equity and brand choice intention: The case of ethnic restaurants - Lu, A.; Gursoy, Dogan; Lu, C. (Elsevier Ltd, 2015)
This study examines the relationships between consumers' authenticity perception and four brand equity dimensions (brand awareness, brand association, perceived quality, brand loyalty), as well as how these four dimensions are interrelated with one another. This study also examines the impact of brand equity on consumers' brand choice intention for ethnic restaurants. Findings clearly indicate that consumers' authenticity perception is a critical determinant of brand equity and brand equity has a significant impact on consumers' brand choice intention. Findings of the present study would provide managers with a better understanding of the important role authenticity plays in ethnic restaurants' brand equity. Managerial implications for better brand equity management are provided.